Farm record keeping - A tool to understand gender differentiated roles and decision power - Rai, Munmun (International Maize and Wheat Improvement Center, 2018)
Presented by Munmun Rai (CIMMYT), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.